Different fungal signatures in ALD and MAFLD - Zhang, Daya; Wang, Qi; Li, Da; Chen, Chen; Lv, Yanting; Huang, Shimei; Zeng, Fan; Huang, Xianfeng; Mao, Fengjiao; Bai, Feihu (Frontiers in Microbiology, 2024)
ObjectiveThis study investigates the differential impact of fecal fungal microbiota on the pathogenesis of alcohol-associated liver disease (ALD) and metabolic-associated fatty liver disease (MAFLD). We aim to delineate distinct microbial patterns across various stages of each disease.MethodsWe conducted fungal internal transcribed spacer 2 (ITS2) sequencing analysis on fecal samples from 48 ALD patients, 55 MAFLD patients, and 64 healthy controls (HCs).ResultsDistinct fungal microbiota profiles were significantly identified between the ALD and MAFLD patients. In the ALD group, genera such as Trichosporon, Davidiella and Asterotremella along with species like Trichosporon unclassified and Davidiella unclassified were elevated compared to those in the MAFLD group. Conversely, Fungi unclassified, Rhizopus, Periconia, and Candida albicans were more prevalent in MAFLD patients. A specific fungal signature comprising Asterotremella_pseudolonga, Malassezia_restricta and Malassezia, was notably effective in differentiating ALD from MAFLD, achieving an area under the curve (AUC) of 0.94. Periconia and Periconia byssoides were more abundant in non-obese MAFLD patients compared to obese MAFLD and HCs. Rhizopus microsporus var. chinensis and var. rhizopodiformis, along with Pleosporales unclassified, were predominantly found in MAFLD patients with moderate to severe hepatic steatosis (HS). The genera Pleosporales_unclassified and the species Candida_albicans were markedly elevated in ALC patients when contrasted with AFL or HCs.ConclusionThis investigation introduces a novel fungal signature that successfully differentiates between ALD and MAFLD, underscoring Pleosporales unclassified, as biomarkers for disease progression in ALD and MAFLD. The findings also suggest a significant role for Periconia in the progression of non-obese MAFLD.